Morphological and Histopathological Characterization of Myxobolus cyprinicola in the Asian Catfish, Silurus triostegus (Heckel, 1843), from Basrah, Iraq - Abbas, Abbas; Awad, Abdul-Hussein; AL-Daraji, Salem (Iraqi Journal of Aquaculture, 2026)
Background: Myxozoan parasites are among the most widespread and pathogenic fish parasites. In Iraq, several Myxobolus species have been reported, yet histopathological impacts remain poorly understood. Aim: The purpose of this work is to offer the first record, morphological characterization, and histological assessment of Myxobolus cyprinicola infecting the Asian catfish Silurus triostegus from the Hammar Marshes in southern Iraq. Methods: A total of Asian catfish were examined, of which were found to be naturally infected. The spores were examined morphologically, measured, and identified using standard taxonomic keys. Infected intestinal tissues were processed for histology using paraffin embedding and H&E staining. Results: M. cyprinicola plasmodial cysts (0.4–1.7 mm) were found in the lamina propria and circular muscle layer. Spores were ellipsoidal (10–12.7 × 9–9.7 μm) with distinct sutural lines and pyriform polar capsules. Histopathological lesions included epithelial atrophy, villous fusion, hemorrhage, muscular degeneration, and vascular congestion. Conclusion: This study documents M. cyprinicola for the first time in Iraq and identifies Silurus triostegus as a new host species. Its presence in intestinal wall indicates significant tissue damage and highlights the parasite’s pathogenic potential.